A Comparison of the Pali and Chinese Versions of the Vangisa-thera Samyutta, a Collection of Early Buddhist Discourses on the Venerable Vangisa - Choong, Mun-Keat (Buddhist Studies Review, 2007)
This article first briefly examines the textual structure of the Vangisathera Samyutta of the Pali Samyutta-nikaya in conjunction with two other versions preserved in Chinese translation in Taisho vol. 2, nos. 99 and 100. Then it compares the main teachings contained in the three versions. These three versions of this collection on the subject of the venerable Vangisa represent three different early Buddhist schools within the Sthavira branch. This comparative study of these three different versions focuses on three major topics: (i) Arhants at the pravarana ceremony; (ii) sensual desire and the way to extinguish it; and (iii) the Buddha’s teachings to Vangisa. It reveals similarities and significant differences in structure and doctrinal content, thus advancing the historical/critical study of early Buddhist doctrine in this area.